Trabalho e mortificação: o humano, o desejo e o consumo - Ribeiro, Sandro Henrique (2018)
In the history of capitalism, the reality of the world of work has always been fraught with deep marks of suffering and each historical moment is likely to present very specific characteristics, molded in the concrete practice of daily life. The contradictions of the process of production of wealth made possible a strengthening of the world of the commodity to the detriment of the human and many reflections were born like effective confrontation to the impositions that fell heavily on the life of the workers. Various elements of working life have gained prominence in Karl Marx’s constructions, from the rigid process of the factory system to the so-called flexibilizations of the new capitalism. In this sense, it will be emphasized some analyzes developed by the Frankfurt School, mistakenly recognized by many theoretical analysis as an outdated critic and commonly framed and interpreted like a idealistic conceptions. Through bibliographic research, theoretical analysis and records of illness at work, it was possible to arrive at several nuances of this suffering, which received attempts at cataloging with heath perspectives of health policies. Together with the intense changes that occurred in the world of production, so did the conceptualizations and records of occupational medicine, in the constant exercises of cataloging and understanding the new diseases, which did not always have a broad presentation of their causes in the organic structure. In this way, much of this suffering escaped technical-quantitative perception and sedimented in the fibers of daily life. With the pace of productivity, the strengthening of the world of merchandise has been intensified to the detriment of the human, who is unceasingly instigated to consumption in the new capitalism’s congigurations: it has become na effective guarantee of reinforcemente from the world of production. In this scenario, advertising constructions have greatly instigated the mechanism of desire which, unlike necessity, can be recognized as the order of the endless. With frankfurtian elaborations and psychoanalytic theorizations it was possible to arrive at a more comprehensive analysis of the products coming from the advertising world and the undeniable relation of the self, present in the traits of social collectivity. It was possible to register ingenious processes that ended up intensifying the situation of suffering in the world of work, through financing programs that fortified the ballasts with the world of the merchandise, causing the individual himself to maintain the feedback and enlargements of the universe of production. Thus, these constructions of the market world, in the logic of accumulation, are processes based on the materiality of existence in which the subject is not only accessed but also a participant in this process.